Towards optimizing metal enhanced fluorescence (MEF) for improved detection of disease biomarkers - Centeno, Anthony Edward Robert (AMG Transcend Association, 2014)
Fluorescent molecules are commonly used for the detection of disease biomarkers. Metal Enhanced Fluorescence (MEF) is a promising strategy for improving the detection sensitivity. This paper describes current research on using Computational Electromagnetics (CEM) as a prediction tool for fluorescent enhancement. Recent published work has shown that for isolated spherical nanoparticles in solution fluorescent enhancement can be predicted with reasonably good accuracy. This work has been extended to consider immobilized particles in periodic arrays formed by colloidal lithography. These kinds of arrays could have potential applications in sensing and bioimaging. The initial results show that coupling between the fluorophore and the metal nanoparticle is extremely complex. The coupling is strongly dependent on the position and electromagnetic polarization of the fluorophore emission with respect to the adjacent metal surface.